2020
DOI: 10.1088/1742-5468/ab6b1a
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of stairs on the bidirectional movement of pedestrians

Abstract: Although bidirectional motion on stairs can be commonly observed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
2
20
2
Order By: Relevance
“…The reason lies in that pedestrians have to maintain a personal space for keeping a high evacuation velocity on the staircase, thus inducing small population density in this experiment. In [20], the average bidirectional velocity is only around 0.4 m s −1 , which is much smaller than in this study (0.88 m s −1 ), so population density can grow to a relatively high value of 6 persons/m 2 . The finding was also verified in unidirectional flow on flat areas [36], which presented that people need more space for their comfort at a higher velocity in straight corridors.…”
Section: Bidirectional Evacuationcontrasting
confidence: 70%
See 4 more Smart Citations
“…The reason lies in that pedestrians have to maintain a personal space for keeping a high evacuation velocity on the staircase, thus inducing small population density in this experiment. In [20], the average bidirectional velocity is only around 0.4 m s −1 , which is much smaller than in this study (0.88 m s −1 ), so population density can grow to a relatively high value of 6 persons/m 2 . The finding was also verified in unidirectional flow on flat areas [36], which presented that people need more space for their comfort at a higher velocity in straight corridors.…”
Section: Bidirectional Evacuationcontrasting
confidence: 70%
“…Given the bidirectional experiment in [20] that had explored bidirectional movement with varying flow ratios, it was found that the full bidirectional flow, i.e. ratio = 0.5, was the most dangerous situation, where average velocity always assumes the minimum value, illustrating that complex interactions exist among individuals during full bidirectional flow.…”
Section: Bidirectional Scenariomentioning
confidence: 99%
See 3 more Smart Citations